Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1126/sciadv.aax8720
|View full text |Cite
|
Sign up to set email alerts
|

Topological charge transport by mobile dielectric-ferroelectric domain walls

Abstract: The concept of topology has been widely applied in condensed matter physics, leading to the identification of peculiar electronic states on three-dimensional (3D) surfaces or 2D lines separating topologically distinctive regions. In the systems explored so far, the topological boundaries are built-in walls; thus, their motional degrees of freedom, which potentially bring about new paradigms, have been experimentally inaccessible. Here, working with a quasi-1D organic material with a charge-transfer instability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…Our previous study demonstrated that the resistivity minimum results from the NI domain wall (NIDW) excitations arising around NI crossover pressure [Fig. 1] [12]. The present experiment with the piston-cylinder pressure cell confirmed the pressure-insensitive resistivity previously suggested by the experiment using the cubic anvil apparatus [33].…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Our previous study demonstrated that the resistivity minimum results from the NI domain wall (NIDW) excitations arising around NI crossover pressure [Fig. 1] [12]. The present experiment with the piston-cylinder pressure cell confirmed the pressure-insensitive resistivity previously suggested by the experiment using the cubic anvil apparatus [33].…”
supporting
confidence: 87%
“…Topological excitations in one dimension (1D) are zerodimensional defects behaving like particles. They are known as solitons and domain walls, which occasionally cause unconventional electrical and magnetic properties [1][2][3][4][5][6][7][8][9][10][11][12]. Notably, the solitons expected to emerge in the neutral-ionic (NI) transition material, tetrathiafulvalenep-chloranil (TTF-CA), are of profound interest in that they can be elementary excitations responsible for electrical and magnetic properties instead of electrons in a Mott-Peierls system, in which charge, spin, and lattice are strongly entangled [13][14][15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings have led to the development of related materials and applications (Frére and Skabara, 2005 ; Pauliukaite et al, 2007 ; Piek et al, 2018 ; Fujihara et al, 2020 ). On the other hand, another type of ICT complexes, i.e., those consist of alternately stacked arrays of the ionized D and A molecules, have recently been attracted attention because they are expected to serve as potential platforms for designing advanced materials such as organic ferroelectrics (Horiuchi and Tokura, 2008 ; Kobayashi et al, 2012 ; Takehara et al, 2019 ), multiferroics (Kagawa et al, 2010 ; Wang and Zhang, 2020 ), and photovoltaics (Nakamura et al, 2017 ). In contrast to the conventional neutral CT complexes, reports on ICT complexes have been largely limited to crystalline solids.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of existing CT complexes reported to date fall into the class of neutral CT complexes with smaller ρ CT values (0 < ρ CT < 0.5), and only those having large ρ CT values (0.5 < ρ CT ≤ 1) are referred to as ICT complexes. The neutral to ionic transition of CT complexes has been induced by applying pressure (Torrance et al, 1981b ; Takehara et al, 2019 ) or at a considerably lower temperature of 81 K for a tetrathiafluvalne- p -chloranil complex (Torrance et al, 1981a ; Okamoto et al, 1991 ). These conditions severely limit the applicability of ICT complexes for device applications.…”
Section: Introductionmentioning
confidence: 99%